Edenville Owls - Parker, Robert B., 1932- (Sleuth Philomel, 2007)
Fourteen-year-old Bobby, living in a small Massachusetts town just after World War II, finds himself facing many new challenges as he tries to pull together his coachless basketball team, cope with new feelings for his old friend Joanie, and discover the identity of the mysterious stranger who seems to be threatening his teacher.